The inhibitory activity of Avicennia marina leaf extract on Enterococcus faecalis as a root canal irrigation material - Prabanita, Amellindha Salsabilah; Soesilo, Diana; Sularsih; Dwi Andriani; Kuntjoro, Mefina; Prasetyo, Eric Priyo (Universitas Airlangga, 2025)
Background: Enterococcus faecalis is considered the most common cause of root canal failure and persistent infection. The standard irrigation solution is 5.25% NaOCl which has drawbacks, such as causing inflammation in the periapical area. New antibacterial agents from natural materials with similar antibacterial properties to chemicals have been developed. Avicennia marina contains flavonoids, saponins, tannins, and avicequinone, which can inhibit bacterial metabolism. Objective: to determine the effect of Avicennia marina leaf extract with various concentrations on the antibacterial inhibitory power of Enterococcus faecalis as a root canal irrigation material. Materials and Methods: The samples were divided into six groups: K+ (5.25% NaOCl), K- (distilled water), P1 (7.5%), P2 (12.5%), P3 (17.5%), and P4 (22.5%). The leaves of Avicennia marina were extracted using ethanol maceration with a rotary evaporator to obtain a concentrated extract, which was then diluted with distilled water to the desired concentrations. The antibacterial effect was tested using the disk diffusion method by applying 0.01 ml of each test sample to sterile paper disks with a sterile micropipette. Results: Inhibition zones were observed as follows: K+ (21.67 mm), P1 (0 mm), P2 (10.50 mm), P3 (13.50 mm), and P4 (14.50 mm). Mann Whitney tests showed significant differences (p < 0.05) between K+ and P1, P2, P3 and P4, as well as between P3 and P4. Conclusion: Avicennia marina leaf extract had antibacterial effects against Enterococcus faecalis at concentrations of 12.5%, 17.5%, and 22.5%.